Perception and socio-determinants on the usage of mobile health applications among publics in Pahang, Malaysia - Johari, Kaiyisah; Firdaus, Mohd Khairul Zul Hasymi; Che Hasan, Muhammad Kamil; Nik Mohd Hatta, Nik Noor Kaussar (Panyapiwat Institute of Management, 2024)
Introduction: Advancement technologies have greatly influenced the day-to-day activities in the current era. Mobile health applications (mHealth apps) are one of the alternatives introduced in response to technological advancement. Infusing health information into the smartphone speculated that may assist an individual to be more alert with their health condition. However, there is limited data published on the use of mHealth apps among Malaysians especially in the eastern region. Hence the study was conducted to determine the perceptions and socio- determinants of the use of mHealth apps among the public in Pahang, one of the states located in the eastern region of Malaysia. Method: A cross-sectional descriptive study was conducted among 207 publics in Pahang from February to June 2023. A set of questionnaires was used in assessing socio-demographic profiles (age, gender, level of education, and level of income) , and perception of the usage of mHealth apps. The perception was measured by using a general perception of mHealth apps, the perception of the impact of mHealth apps and the perception of the characteristics of mHealth apps. Result: Majority of respondents showed a high level of perception of the use of mHealth apps. Age showed a significant association with the general perception, perception of the impacts of mHealth apps and perception of ideal characteristics of mHealth app (p < 0. 05) , while the others showed no significant findings. Conclusion: General publics in Pahang shows a high- level perception on the use of mHealth apps. Hence, it shows that mHealth apps is applicable to be used in delivering health information to the public in Pahang. The positive perception of the mHealth app will be helpful for the nurse to imbue technological advancement into the app for better sharing of health information.